Size distributions and health risks of particulate trace elements in rural areas in northeastern China - Wang, Jian; Pan, Yuepeng; Tian, Shili; Chen, Xin; Wang, Lu; Wang, Yuesi (Atmospheric research, 2016)
To characterize the airborne trace elements (Be, Na, Mg, Al, K, Ca, Mn, Fe, Co, Ni, Cu, Zn, Se, Mo, Ag, Cd, Ba, Tl, Pb, Th and U) in rural areas in northeastern China, size-resolved aerosols were collected bi-weekly from March 2013 to February 2014 at two farmland sites in Shenyang (SHY) and Hailun (HLZ), a grassland site in Tongyu (TYU) and a forest site in the Changbai Mountain (CBS). The results showed that most trace elements (TEs) exhibited significantly higher concentrations at SHY than those at HLZ, TYU and CBS. All of the sites exhibited higher values in spring/winter than those in summer/autumn. Industrial imprints on the concentrations and size distributions of Pb and Cd were found at SHY, as supported by an air-mass backward-trajectory analysis and the abundance of sulfate and heavy metals. Due to the frequent influence of sand dust, the size distributions of Ca and Ba at the grassland site near Inner Mongolia had dominant peaks at 5.8–9μm, in contrast to the other agricultural and forest sites, which peaked at 4.7–5.8μm. In addition, the concentrations and the enrichment factors (EFs) of the TEs in this study increased as the size range decreased from coarse to fine particles, resulting in the highest carcinogenic (e.g., Pb) and non-carcinogenic (e.g., Mn) risks at 1.1–2.1μm. Overall, the results highlight the severe pollution of heavy metals in northeastern China, particularly in agricultural regions that are subject to anthropogenic influences. Mitigating atmospheric TEs in the studied region, an important commodity grain base in China, is urgently needed to protect the environment and human health from toxic metals. •Size-resolved aerosol trace elements varied under different land-use types.•Heavy metals risks in fine particles increased significantly in the past decade.•Pb and Mn had the highest carcinogenic and non-carcinogenic risks, respectively.•Health risks were higher at the sites of farmland than grassland and forest.